2008
DOI: 10.1111/j.1751-7176.2008.08575.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium, Magnesium, and Calcium: Their Role in Both the Cause and Treatment of Hypertension

Abstract: Despite advances in the prevention and treatment of hypertension over the past decade, hypertension remains an important public health challenge. Recent efforts to reduce the prevalence of hypertension have focused on nonpharmacologic means, specifically diet. An increased intake of minerals such as potassium, magnesium, and calcium by dietary means has been shown in some but not all studies to reduce blood pressure in patients with hypertension. This review will discuss the roles of potassium, magnesium, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(165 citation statements)
references
References 75 publications
4
147
1
7
Order By: Relevance
“…Experimental studies have suggested several ways that dietary calcium may affect blood vessels (18). It might also affect blood pressure in relation to concomitant levels of sodium excretion (19).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have suggested several ways that dietary calcium may affect blood vessels (18). It might also affect blood pressure in relation to concomitant levels of sodium excretion (19).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the impact of calcium on BP is associated with its effect on vascular smooth muscles, Ca-dependent hormones (PTH, 1.25 dihydroxyvitamin D3, calcitonin) activity of reninangiotensin system, the activity of the sympathetic nervous system, metabolism of other electrolytes, calcium-binding proteins, and the concentration www.cardiologyjournal.org of free intracellular calcium, whereas the role of other elements in the regulation of BP value may be largely linked to their influence on calcium metabolism [27]. In the studies, an inverse relationship between the content of potassium, calcium and magnesium in the diet and the BP value is observed [28,29]. Meta-analyses show a small reduction of SBP from 0.9 to 1.4 mm Hg and DBP from 0.2 to 0.8 mm Hg during calcium supplementation (400-2,000 mg/d) [30].…”
Section: Discussionmentioning
confidence: 99%
“…In aggregate, studies indicate that increased potassium intake lowers BP, whereas the effects of magnesium and calcium on BP are uncertain. [12][13][14] The effects of these micronutrients on PRA is inconsistent, with some, …”
Section: Discussionmentioning
confidence: 99%